A Z-Scheme Heterojunction g-C3N4/WO3 for Efficient Photodegradation of Tetracycline Hydrochloride and Rhodamine B - Yongxin Lu; Shangjie Gao; Teng Ma; Jie Zhang; Haixia Liu; Wei Zhou (Nanomaterials, 2025)
The construction of heterojunctions can effectively inhibit the rapid recombination of photogenerated electrons and holes in photocatalysts and offers great potential for pollutant degradation. In this study, a Z-scheme heterojunction g-C3N4/WO3 photocatalyst was synthesized using a combination of hydrothermal and calcination methods. The photocatalytic degradation performance was tested under visible light; the degradation efficiency of Rh B reached 97.9% within 15 min and that of TC-HCl reached 93.3% within 180 min. The excellent photocatalytic performance of g-C3N4/WO3 composites can be attributed to the improved absorption of visible light, the increase in surface area, and the effective separation of photogenerated electron–hole pairs. In addition, after four cycles of experiments, the photocatalytic performance of g-C3N4/WO3 did not decrease obviously, remaining at 97.8%, which proved that the g-C3N4/WO3 heterojunction had high stability and reusability. The active radical capture experiment confirmed that h+ and ·O2− played a leading role in the photocatalytic degradation. The Z-scheme heterojunction g-C3N4/WO3 designed and synthesized in this study is expected to become an efficient photocatalyst suitable for environmental pollution control.